Enhanced Methane Generation During Theromophilic Co‐Digestion of Confectionary Waste and Grease‐Trap Fats and Oils with Municipal Wastewater Sludge. (1st February 2013) - Gough, Heidi L.; Nelsen, Diane; Muller, Christopher; Ferguson, John
Abstract : Recent interest in carbon‐neutral biofuels has revived interest in co‐digestion for methane generation. At wastewater treatment facilities, organic wastes may be co‐digested with sludge using established anaerobic digesters. However, changes to organic loadings may induce digester instability, particularly for thermophilic digesters. To examine this problem, thermophilic (55 °C) co‐digestion was studied for two food‐industry wastes in semi‐continuous laboratory digesters; in addition, the wastes' biochemical methane potentials were tested. Wastes with high chemical oxygen demand (COD) content were selected as feedstocks allowing increased input of potential energy to reactors without substantially altering volumetric loadings. Methane generation increased while reactor pH and volatile solids remained stable. Lag periods observed prior to methane stimulation suggested that acclimation of the microbial community may be critical to performance during co‐digestion. Chemical oxygen demand mass balances in the experimental and control reactors indicated that all of the food industry waste COD was converted to methane.